Adsorption of Natural Product Compound, Goniothalamin, by Dodecyltrimethylammonium-Montmorillonite - Jirawan Noichan (Science Faculty of Chiang Mai University, 2019)
An organoclay (dodecyltrimethylammonium-montmorillonite) was prepared by the ion exchange reaction between quaternary ammonium surfactant, dodecyltrimethylammonium ion, and sodium ion in the interlayer space of montmorillonite. The modication changed the surface property of the clay mineral from hydrophilic to hydrophobic property and significantly increased the basal spacing of montmorillonite to be 1.72 nm. The adsorption of goniothalamin in dodecyltrimethylammonium-montmorillonite was carried out by solid-liquid reaction. The product was characterized by powder X-ray diffraction, infrared spectroscopy, thermal analysis and elemental (CHN) analysis. The presence of the alkylammonium ion and goniothalamin in the product suggested the adsorption of goniothalamin and dodecyltrimethylammonium ion into interlayer space of montmorillonite.